2020
DOI: 10.1111/aji.13316
|View full text |Cite
|
Sign up to set email alerts
|

Specific inflammatory profile in each pregnancy complication: A comparative study

Abstract: Pre-eclampsia (PE), preterm birth (PTB) and intra-uterine growth restriction (IUGR) affect 5%-12% of pregnancies. They have been associated with placental inflammation, although the detection of inflammatory mediators in the maternal circulation is still controversial. Our goal was to determine the inflammatory changes occurring in the second part of pregnancy to identify profiles distinguishing pathological pregnancies from each other.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 43 publications
1
10
0
1
Order By: Relevance
“…It is important to point out that there is not an international standardization in the techniques to report harmonized results either. However, some other groups reported similar cytokine concentrations to our study values (19,(39)(40)(41)(42)(43)(44)(45)(46).…”
Section: Inflammatory Profile and Osasupporting
confidence: 89%
“…It is important to point out that there is not an international standardization in the techniques to report harmonized results either. However, some other groups reported similar cytokine concentrations to our study values (19,(39)(40)(41)(42)(43)(44)(45)(46).…”
Section: Inflammatory Profile and Osasupporting
confidence: 89%
“…For comparison, in Study II CXCL10 did not significantly differ between groups of PTL, PPROM, antenatal controls and controls in labour at term, neither analysed by multiplex bead assay nor by PEA. Elevated levels of CXCL10 have previously been associated with preeclampsia [218][219][220] , in accordance with the inflammatory properties of CXCL10. Regarding PTB, previous studies have not demonstrated clear associations with levels of CXCL10 220,221 although CXCL10 has been found to be increased in inflammatory conditions of the placenta 222 which might precede PTB.…”
Section: Associations Between the Oxylipins 910-dihode 1112-dihetre 8-hete And Preterm Birthmentioning
confidence: 63%
“…Elevated levels of CXCL10 have previously been associated with preeclampsia [218][219][220] , in accordance with the inflammatory properties of CXCL10. Regarding PTB, previous studies have not demonstrated clear associations with levels of CXCL10 220,221 although CXCL10 has been found to be increased in inflammatory conditions of the placenta 222 which might precede PTB.…”
Section: Associations Between the Oxylipins 910-dihode 1112-dihetre 8-hete And Preterm Birthmentioning
confidence: 63%
“…Together with an overall WAT dysfunction [ 8 ], inflammation and oxidative stress are considered some of obesity’s key mechanisms. Obesity-related pregnancy complications are associated with inflammatory and oxidative activities as well [ 15 , 16 ]. Inhibiting these processes in WAT could therefore prevent short-term and persistent damage to mother and child.…”
Section: Introductionmentioning
confidence: 99%